THE DESIGN TURN AND ITS PHILOSOPHICAL REFLECTIONS - Huang, Yuan (European journal for philosophy of religion, 2023)
This study investigates how collaboration between design research and technological philosophy can benefit both fields. More emphasis must be placed on the quality and quantity of philosophical education and its application within the framework of "workmanship philosophy," given the available tools for artistic expression. In expressions instruction, several tactics and approaches should be utilized, and students should be capable of analyzing and comprehending works of art using a variety of approaches. Is it required to utilize philosophical terminology in the illustration of handicraft philosophy? Is it feasible, on the other hand, that philosophical terminology provides a vulnerability for these problems to be examined and multiple answers to be found? Nonetheless, we must be interested in Plato's discourse and the significance of Aristotle's poetics to create even more appealing statements. Instead of emphasizing a complete education in philosophy, art students must learn and comprehend the properties of knowledge that form the foundation of philosophy. This assists in determining the placement and significance of philosophy in speech. Based on three contextual studies employing technology philosophy hypotheses and methodologies in a planning setting, we will explain how these businesses profited from a more reflective viewpoint. Aside from contemplating and debating, one may argue that the Philosophy of Technology is still functioning. As well as technology philosophy with the mind, there is also technology philosophy with the hands. About the prior experimental shift in Philosophy of Technology, we refer to this partnership as the "Useful Approach in Philosophy of Technology." Based on three contextual studies using technology philosophy hypotheses and methods in a planning environment, we will explain how these companies benefited from a more reflective perspective. Other than thinking and discussing, one may claim that the Philosophy of Technology is still active. Technology philosophy with the head, as well as technology philosophy with the hands As a result, we refer to this collaboration as the 'Useful Approach in Philosophy of Technology,' in reference to the preceding experimental turn in Philosophy of Technology.